2016
DOI: 10.1007/s00787-015-0808-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, incidence, and natural course of anorexia and bulimia nervosa among adolescents and young adults

Abstract: We aimed to assess the prevalence, incidence, age-of-onset and diagnostic stability of threshold and subthreshold anorexia nervosa (AN) and bulimia nervosa (BN) in the community. Data come from a prospective-longitudinal community study of 3021 subjects aged 14-24 at baseline, who were followed up at three assessment waves over 10 years. Eating disorder (ED) symptomatology was assessed with the DSM-IV/M-CIDI at each wave. Diagnostic stability was defined as the proportion of individuals still affected with at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
138
1
14

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(161 citation statements)
references
References 66 publications
8
138
1
14
Order By: Relevance
“…Overwhelmingly affecting adolescent and emerging adult women, eating disorders can have lasting complications including increased risk for depression, obesity, substance use, and health problems (Wilson, Becker, & Heffernan, 2003). The transition to college and young adulthood might be an especially vulnerable period in the development of pathological eating behaviors (Delinsky & Wilson, 2008;Nagl et al, 2016;Sassaroli & Ruggiero, 2005). The college environment involves heightened competition and stressors that increase the risk of multiple forms of psychopathology, particularly in the first year (Conley, Kirsch, Dickson, & Bryant, 2014;Dusselier, Dunn, Wang, Shelley, & Whalen, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…Overwhelmingly affecting adolescent and emerging adult women, eating disorders can have lasting complications including increased risk for depression, obesity, substance use, and health problems (Wilson, Becker, & Heffernan, 2003). The transition to college and young adulthood might be an especially vulnerable period in the development of pathological eating behaviors (Delinsky & Wilson, 2008;Nagl et al, 2016;Sassaroli & Ruggiero, 2005). The college environment involves heightened competition and stressors that increase the risk of multiple forms of psychopathology, particularly in the first year (Conley, Kirsch, Dickson, & Bryant, 2014;Dusselier, Dunn, Wang, Shelley, & Whalen, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…EDs most typically onset between adolescence and young adulthood (Hudson, Hiripi, Pope, & Kessler, 2007; Nagl et al, 2016; Stice, Marti, Shaw, & Jaconis, 2009), and the college years are associated with a significant reduction in students’ healthy lifestyle behaviors, which has implications for cardiovascular health and individuals’ weight gain trajectories (Arts, Fernandez, & Lofgren, 2014; Nelson, Larson, Barr-Anderson, Neumark-Sztainer, & Story, 2009; Nelson, Story, Larson, Neumark-Sztainer, & Lytle, 2008; Spring et al, 2014). Indeed, research has indicated that adults aged 18–29 years are more likely to develop obesity than individuals of older ages (Mokdad et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The current study therefore assessed the overlap between eating pathology and a range of autistic traits in a large sample of university students, and also assessed whether emotions mediate this relationship by exploring a new autistic-emotional model of eating pathology. Although the official ED prevalence rate is around 0.5-3%, depending on the specific ED diagnosis, ED symptoms in the general population have been found to be as high as 12%, suggesting that it is meaningful to explore risk factors, such as ASD traits, in general population samples (Nagl et al, 2016).…”
Section: Introductionmentioning
confidence: 99%